Evolução termocronológica do sistema de falhas Senador Pompeu-CE - Cavalcante, Antonio Sânzio ávila Cavalcante (2006)
The region of the Senador Pompeu Shear Zone (SPSZ), in the North Tectonic Domain of the Borborema Province (BP), has its recent history associated with to South Atlantic Ocean formation event at the Jurassic. A lot of geologics models have discussed about crustal axis elevation in local scale and large scale (Borborema Province), relative to importants regionals tectonics directions of it. The identification and the relationship among this surfaces, stepped in many topographyc levels by tectonics mecanisms, is dificult because of the erosion process on it. Over there, sedimentary deposits is complex and it has not biostratigraphyc record in continental deposits. The analysis metodology on apatita fission-track, in the region of the SPSZ, purpose the more knowledge about morphotectonics mecanisms of the area and the impruvement of its morphotectonics models. For this, it was moleled the age and thermal history of the 11 apatites samples collected on both sides of this shear zone, taking relationships among other results of the thermochronology studies in the BP. Based on the thermal studies in this search, the region of the BP developed on two distint cooling events, separated for one period of relative stabilited. The first episode occur between 130 and 90 M.y., has been began when the samples cross the 120°C isoterm for last time and fineshed at 70°C. The second moment of the cooling process was began about 30 M.y., when the temperature was 90°C, from this to the equlibrium with present surface temperature at 30°C. Some evidences indicated a relacionship between thermal episodes and uplift events of the regional relief. The fundaments of the interpretation was based mainly on comparatives studies among results of the thermochronology analysis and geologics studies about BP. Nóbrega et al.(2005), e.g., on studies about the Portalegre Shear Zone, got similar results on SPSZ, with some details relative to local tectonic activity. Morais Neto et al. (2000) interpreted two importants cooling events in the BP based on their regional studies, that can be associated to regional uplift events. When Assine (1992) studied the stratigraphyc sequences of the Araripe Basin, in the south of Ceará state, conclude that the abrupt return to continentals condictions from the last sedimentar sequency (albiano-cenomaniane) indicate a regional uplift of the NE region of the Brazil at the 100 M.y., in the Albiano Intermediate/Superior. This ages are compatible to termal model of the SPSZ. This two periods of the thermal history of the BP are completely registered in the apatites samples just one age groups of the fission-track, that it is the most ancient age groups. This one suggest it has happened in response to heating before 75 M.y and it has erased the last report of the first moment relief evolution of the BP. The NNE-SSW and E-W structure reativation can have created ideal condictions for heating and local elevations of the geothermal gradients. The equilibrium between the apatites temperatures of this groups and the regionais temperatures took place about 50 M.y., when the samples of the two ages groups had a simillar evolution to present surfaces temperatures